CONSIDERING TOLERANCE EDUCATION BETWEEN RELIGIOUS SECTS: A Case Study of Sunni-Syi'ah Sects in Karang Gayam and Blu'uran Villages of Sampang - Wasik Wasik; Rahman Rahman; Syamzan Syukur; Moh. Mujibur Rohman (IAIN Ponorogo, 2023)
In Islamic character education, tolerance is one of the values that must be grown as a person's primary virtue or exemplary character. This study aims to determine (1) the concept of tolerance character formation, (2) the process of applying tolerance values, and (3) supporting and inhibiting factors in the formation of tolerance. The method used in this research is a qualitative approach with a case study type. The research results are (1) Forming a community devoted to Allah SWT. based on the al-Quran and Hadith of the Prophet Muhammad and reviving da'wah and ukhuwah Islamiyah in their friendship interactions. (2) Providing understanding through tausiyah or Islamic studies from mu'allim, attending and actively participating in recitation events. (3) The supporting factors are public awareness of religion, support from the local apparatus, and the charismatic kiai. At the same time, the inhibiting factors are the busyness of each resident's work and the fanaticism of the Ahl al-Sunnah wa al-Jamaah sect.